Collaborative Project Usage Analysis Steam Integration Towards Characters and Student Creativity - Elisa Mutiara Br Sembiring; Amanda Syahri Nasution; Nurdalilah; Haryati Ahda Nasution (EDUCATION JOURNAL OF INDONESIA, 2025)
This study aims to analyze the significant influence between the use of STEAM integrated collaborative projects on the character and creativity of students of RK Delidunia Delitua Private Middle School on the KPK and FPB materials. This study uses a mixed method research design that combines quantitative and qualitative methods. This study uses an explanatory sequential design model. The stages in this study are the researcher conducting quantitative data analysis by analyzing data for test instruments in the form of essays, questionnaire instruments and interview guidelines. The population in this study were all students of class VII of RK Deliwarni Delitua Private Middle School consisting of 3 classes with a total of 93 students. The sample in this study used one class using a purposive sampling technique, namely data collection based on certain considerations. The sample to be analyzed was 6 students, each of whom was seen based on the level of ability of 2 high students, 2 medium students, 2 low students based on considerations of MID results, interviews, and observations. This study used a character questionnaire and creativity test that had gone through an expert assessment process and instrument trials, and were declared valid and reliable. Based on these findings, it shows that there is a significant influence between the use of STEAM integrated collaborative projects on student creativity in KPK and FPB materials. The results of this study are also expected so that schools can provide special training for teachers in teaching using projects in order to help students achieve the desired learning.   Keywords: STEAM, Character, Creativity Integrated Collaborative Project